2021
DOI: 10.2298/jsc201230037s
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, spectroscopic characterization, DFT, oxygen binding, antioxidant activity on Fe(III), Co(II) and Ni(II) complexes with a tetradentate ONNO donor Schiff base ligand

Abstract: The Schiff base ligand, namely (7E)-N-benzylidene-2-styrylbenzena-mine1,2-diamine-2,4-dihydroxy-phenol, (L), was synthesized from condensation of 2,4-dihydroxybenzaldehyde with o-phenylenediamine. The reaction of the ligand with Fe(III), Co(II) and Ni(II) salts in a 1: 1 ratio yielded three complexes 1-3. Different analytical tools like elemental analysis, ESI-mass spectra, FT-IR, conductivity, electronic spectra, magnetic susceptibility, NMR and EPR mea-surements are used to elucidate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…As well as the free ligand solution in blank DMSO exhibits medium inhibition zones (10-17) mm toward Staphylococcus aureus and Escherichia coli bacteria, whereas no remarkable antifungal, which may be reasonable in high polarity of the triazole structure [22]. Furthermore, the solutions of Ni(II) and Zn(II) displayed the lowest activity toward the E. coli and S. aureus bacteria compared with the control drug of azithromycin (10 ppm), which mainly resulted from the ionic character of chloride ions in the outer sphere of their chemical structures [10,21]. It is observed that the solutions of Pt(IV) and Pd(II) showed greater activity against Candida albicans and Aspergillums favus which are close to the activity of control Miconazole antifungal drug of 10 ppm concentration.…”
Section: Antimicrobial Studymentioning
confidence: 99%
“…As well as the free ligand solution in blank DMSO exhibits medium inhibition zones (10-17) mm toward Staphylococcus aureus and Escherichia coli bacteria, whereas no remarkable antifungal, which may be reasonable in high polarity of the triazole structure [22]. Furthermore, the solutions of Ni(II) and Zn(II) displayed the lowest activity toward the E. coli and S. aureus bacteria compared with the control drug of azithromycin (10 ppm), which mainly resulted from the ionic character of chloride ions in the outer sphere of their chemical structures [10,21]. It is observed that the solutions of Pt(IV) and Pd(II) showed greater activity against Candida albicans and Aspergillums favus which are close to the activity of control Miconazole antifungal drug of 10 ppm concentration.…”
Section: Antimicrobial Studymentioning
confidence: 99%